Enantioselective synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine - Pandey, Satyendra Kumar; Kumar, Pradeep (Tetrahedron Letters, 2006)
An efficient and short synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine 1a-b is described using Sharpless asymmetric dihydroxylation and regioselective nucleophilic opening of a cyclic sulfite as the key steps. (c) 2006 Elsevier Ltd. All rights reserved.